The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.5534/wjmh.180100
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shock Wave Therapy in Peyronie's Disease: Clinical Efficacy and Safety from a Single-Arm Observational Study

Abstract: Purpose In this study, we aimed to determine the role of extracorporeal shockwave therapy (ESWT) in the management of Peyronie's disease (PD). Materials and Methods A total of 325 patients suffering from PD were enrolled in this single-arm clinical study. All patients were received ESWT using a schedule of 1 treatment/wk. Penile curvature was measured by a goniometer after intracavernosal drug-induced erection using Alprostadil. Plaque size was measured with a ruler and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…In another recent study, Di Mauro et al demonstrated that ESWT decreased plaque size, penile curvature, and pain assessed by visual analogue scale (p<0.001). They also showed that ESWT might improve an erectile function measured by IIEF and increase a penile length in erection (p<0.001) [62].…”
Section: Extracorporeal Shock Wave Therapymentioning
confidence: 93%
“…In another recent study, Di Mauro et al demonstrated that ESWT decreased plaque size, penile curvature, and pain assessed by visual analogue scale (p<0.001). They also showed that ESWT might improve an erectile function measured by IIEF and increase a penile length in erection (p<0.001) [62].…”
Section: Extracorporeal Shock Wave Therapymentioning
confidence: 93%
“…It has been shown that younger age at disease onset and the presence of baseline vascular comorbidities (i.e., diabetes and dyslipidemia) demand even more urgency for early recognition and prompt intervention because of a higher risk for disease progression [ 25 36 ]. Retrospective series have proven that patients younger than 40 years are more likely to ask for treatment sooner, present with multiple palpable plaques and have at least one cardiovascular risk factors, as compared with older subjects.…”
Section: Natural Historymentioning
confidence: 99%
“…Treatment of PD includes both medical and surgical approaches and the management is tailored to the phase of the disease, the degree of deformity, the quality of the erections and patient's choice [ 4 9 10 ]. Currently, intralesional injections of corticosteroids and verapamil represent the most common treatments offered for the management of acute phase of PD [ 10 11 ].…”
Section: Introductionmentioning
confidence: 99%